2007
DOI: 10.1016/j.molcel.2006.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a 14-3-3 Coordinated Hexamer of the Plant Plasma Membrane H+-ATPase by Combining X-Ray Crystallography and Electron Cryomicroscopy

Abstract: Regulatory 14-3-3 proteins activate the plant plasma membrane H(+)-ATPase by binding to its C-terminal autoinhibitory domain. This interaction requires phosphorylation of a C-terminal, mode III, recognition motif as well as an adjacent span of approximately 50 amino acids. Here we report the X-ray crystal structure of 14-3-3 in complex with the entire binding motif, revealing a previously unidentified mode of interaction. A 14-3-3 dimer simultaneously binds two H(+)-ATPase peptides, each of which forms a loop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
228
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(250 citation statements)
references
References 44 publications
11
228
0
4
Order By: Relevance
“…S1). Furthermore, the N-terminal part of RGS3 contains a phosphorylated 14-3-3 binding motif (sequence RRRTHpS 264 EGS), which is presumably docked in the ligand binding groove of 14-3-3, as has been observed in other structures of 14-3-3 protein complexes (21,22,24,25,44). Therefore, the rigid body modeling of the 14-3-3⅐pRGS3 complex was performed using the crystal structures of 14-3-3 (21) and RGS domain of RGS3 (27) (Protein Data Bank (PDB) codes 1qjb and 2oj4, respectively).…”
Section: Biophysical Characterization Of the 14-3-3⅐prgs3 Proteinmentioning
confidence: 73%
See 1 more Smart Citation
“…S1). Furthermore, the N-terminal part of RGS3 contains a phosphorylated 14-3-3 binding motif (sequence RRRTHpS 264 EGS), which is presumably docked in the ligand binding groove of 14-3-3, as has been observed in other structures of 14-3-3 protein complexes (21,22,24,25,44). Therefore, the rigid body modeling of the 14-3-3⅐pRGS3 complex was performed using the crystal structures of 14-3-3 (21) and RGS domain of RGS3 (27) (Protein Data Bank (PDB) codes 1qjb and 2oj4, respectively).…”
Section: Biophysical Characterization Of the 14-3-3⅐prgs3 Proteinmentioning
confidence: 73%
“…Despite the large number of 14-3-3 binding partners, only two crystal structures of 14-3-3 complexes with the protein ligand of a size that exceeds the consensus recognition motifs have been solved: the 14-3-3⅐serotonin N-acetyltransferase (AANAT) complex (24) and the 14-3-3⅐C-terminal region of the plant plasma membrane H ϩ -ATPase complex (25). These structures revealed that the primary interactions between 14-3-3 and its protein ligand take place within the ligand binding groove where the segment containing the recognition motif binds, similarly as seen in complexes of 14-3-3 isoforms with short phosphopeptides (21,22,44).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, 14-3-3 proteins are believed to trigger conformational changes in their targets, leading to alterations in activity, stability, oligomerization, or cellular localization of binding partners (36). Although numerous crystal structures of 14-3-3 proteins have been determined in both the apopeptide-bound and the phospho-peptide-bound state (37), to date, their specific mode of action has been established in only two cases: the increase in substrate affinity of serotonin N-acetyltransferase in the 14-3-3 complexed state (33) and the oligomerization of plant plasma membrane ATPase (34).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, 14-3-3 could act by inducing integrin clustering, in a similar way that has been observed for 14-3-3s to induce hexamer formation of a P-type H ϩ -ATPase. 38 On the other hand, 14-3-3 could induce some further interactions of the integrin cytoplasmic domain, for instance by favoring certain conformations of the tail. It is apparent that Rac1/Cdc42 activation is downstream of 14-3-3-integrin interaction.…”
Section: Discussionmentioning
confidence: 99%